Identification of Thermophysical and Rheological Properties of SAE 5w-30 with Addition of Hexagonal Boron Nitride - Reyhandi Katon Asmoro; Poppy Puspitasari; Avita Ayu Permanasari; Muhammad Ilman Hakimi Chua Abdullah (TRANSMISI, 2023)
This research uses SAE 5W-30 lubricant base material with the addition of Hexagonal Boron Nitride (hBN) nanoparticle additives. This study aims to analyze the thermophysical and rheological properties of lubricants with the addition of nanoparticles. The method in this study uses a two-step method where nanoparticles are first prepared separately, then added with nanoparticles with varying volume fractions of 0.05%, 0.10%, 0.15% into the base fluid as a processing step. The next step is the stirring process using a magnetic stirrer, and ultrasonic homogenizer process.  Furthermore, the nanolubricant was tested for thermophysical properties including viscosity, density, thermal conductivity, and sedimentation.